Geographical modelling of patient episode flows and hospital catchment populations: a case study in Northern Ireland - Hindle, Adam J.; Hindle, Giles A.; Hindle, Tony (Health Systems, 2013)
© 2012, Copyright © 2012, Operational Research Society Ltd. This paper describes the development of a decision support framework, which contributed to the strategic management of radical changes in hospital services in Northern Ireland. The approach employed geographical modelling to estimate patient episode flow effects between geographical areas and hospitals under different hospital configurations. Such effects are central to the evaluation of key strategic issues such as catchment population characteristics (and the funding of such), capacity planning and achievement of access/travel time targets. The approach is illustrated with an evaluation of a new-build hospital development in a region within the Province. With respect to the modelling of episode flows, this research has investigated proximity to the nearest ‘appropriate’ hospital as a primary explanatory factor determining hospital choice and has explored ways of defining and quantifying appropriateness.
Keywords: OR in health services; Decision support systems; Hospitals; OR in strategic planning